Changes in the Socio-Economic Pattern of Spanish-American Cities With Special Reference to Colonial Town Centres - Gormsen, E. (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1980)
This paper outlines some of the key changes in the spatial distribution of functions and social classes in Spanish-American cities, with Puebla, Mexico, used as a case study. Among the factors which influence the future of the cities is the changing social structure of the inner zone. Upper class families have moved into modern residential areas while their large colonial patio-houses have been transformed into lower class multi-family quarters known as vecindades.